ZAKAT FITRAH: MANAGEMENT, TRADITION, AND MEANING OF EIDAL-FITR - Perdana, Dian Adi; Tunali, Fatma (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
Zakat as a source of state income, representing zakat for Muslims to approve the spiritual ties of mankind. In this era, discussing zakat which is included in the duties of the authorities means he needs to improve continuity by helping muzzaki either by establishing institutions to facilitate the process of raising zakat funds, because this requires government assistance in improving the economy of the people. The establishment of institutions that represent government programs to overcome domestic economic and religious problems. Urgency about managing zakat, zakat fitrah with an administration system that is also good so that approval and management of zakat can be accounted for, taking into account the most important aspects of zakat management, goods and can also be in the form of money, zakat distribution media can be through mosques, social foundations, etc or directly distributed individually, the time of zakat payment and zakat payment channels. The essence of zakat fitrah over the significance of Eid al-Fitr is so important to human life. That it has meaning for humans who teach humans to share and give alms, gives happiness to those who are weak and unable, makes food for visitors of rice and other foods, ask for value one after one and another for one after another.